Global research publications on irrational use of antimicrobials: call for more research to contain antimicrobial resistance - Waleed M. Sweileh (BMC, 2021)
Abstract Background Irrational use of antimicrobials is highly prevalent. It is a major driving factor for antimicrobial resistance (AMR). Research on irrational antimicrobial use is important for developing policies and regulations to combat and contain AMR. The present study aims to provide an overview of research publications on the irrational use of antimicrobials at the national and global levels. Methods Publications on irrational use of antimicrobials were extracted from Scopus using a wide range of relevant keywords for the study period from 1980 to 2020. Results In total, 656 publications on irrational use of antimicrobials were found. The bulk of publications in this field were about irrational use in humans. A limited number of publications were found on the irrational use of antimicrobials in the context of veterinary and environment. The number of publications, contributing countries, and the mean number of authors per article increased with time, most notably in the last decade. Authors from 105 different countries participated in publishing the retrieved articles with 22 (21.0%) participated in 10 or more publications. The United States led with 140 (21.6%) articles followed distantly by China (n = 49, 7.5%), India (n = 45, 6.9%), and the United Kingdom (n = 45, 6.9%). Countries in the South-East Asian region (n = 69, 10.5%) and the African region (n = 42, 6.4%) made the least contribution. The list of most frequent author keywords included "antimicrobial stewardship" and "community pharmacies". The research themes focused on the hospital-based rational use of antimicrobials and the self-medication practices with antimicrobials in the community. In total, 420 different journals participated in publishing the retrieved documents. The Plos One journal (17, 2.6%) ranked first. The retrieved articles received an average of 15.6 citations per article and an h-index of 52. The most frequent antimicrobials encountered in the retrieved literature were penicillin, cephalosporin, and fluoroquinolones while the most frequently encountered pathogens were S. aureus and P. aeruginosa. Conclusion Research on the irrational use of antimicrobials is needed from all countries and regions to implement appropriate policies to contain the AMR. Research on irrational use of antimicrobials in the context of veterinary is needed.